Personal Brand and Consumer Purchase Intention: The Mediating Role of Perceived Emotional Value - Liu, Jing; Chelliah, Shankar (Journal of Ecohumanism, 2025)
This study investigates the relationship between personal brand and consumer purchase intention, with a specific focus on the mediating role of perceived emotional value. In today’s highly competitive marketplace, personal branding has emerged as a powerful tool for influencing consumer behavior. While previous research has explored the direct impact of personal brand on purchase intention, the mechanisms through which it exerts this influence remain less clear. This study proposes that perceived emotional value—a consumer’s emotional response and attachment to a brand—plays a critical mediating role in this process. Data were collected from telecommunication of large- and mid-sized companies in China. Survey data from 271 team members were tested using PLS-SEM modeling analysis. By examining a sample of consumers across various industries, the study finds that personal branding significantly enhances purchase intention when consumers perceive emotional value in the brand. These findings highlight the importance of emotional engagement in personal branding strategies and suggest that brands seeking to increase consumer purchase intentions should prioritize cultivating emotional connections. The research offers theoretical contributions to the understanding of personal branding and practical insights for marketers looking to optimize consumer decision-making through emotional value creation.